The influence of age on cyclic tensile strain-induced differentiation and apoptosis in mesenchymal stem cells - McKayed, Katey (Trinity College (Dublin, Ireland). Department of Physiology, 2012)
Mesenchymal stem cells, or MSCs, are adult progenitor cells capable of differentiating into specialised skeletal cells such as chondrocytes, osteocytes and adipocytes. Under the appropriate conditions, these cells can be manipulated in vitro for the development of new skeletal tissue such as bone or cartilage. Thus, interest has been focused on MSCs as a promising cell source for use in tissue engineering, which holds considerable potential in the field of regenerative medicine for developing therapies to treat osteochondral disease.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin